Application and Development of Biomimetic Solid-State Nanopore in Biosensing Technique - Ma, Aorui (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Biomimetic solid-state nanopore is a nano-level technology, which can be effectively used for many detection work, including DNA sequencing. The design of biomimetic solid-state nanopore is inspired by biological ion channels. Biomimetic solid-state nanopore displays many advantages. It can increase the processing characteristics while it can also ensure the performance of similar biological ion channels. It also exhibits controllable surface chemical properties, making biomimetic solid nanopores have more application space. When compared with traditional biosensors, biomimetic solid nanopores have many advantages such as low price, high sensitivity and high specificity. At the same time, biomimetic solid-state nanopores have full help for medicine, analytical chemistry, materials science, single molecule biophysics, single molecule in vitro diagnostics, and genetics. Therefore, in this work, the working mechanisms of several biosensors are introduced. In addition, the applications of nanopores in biosensing are outlined. Besides, the circuit design schemes for improving the efficiency of nanopore has been discussed. In conclusion, the help of nanopores at the single-molecule level is undoubtedly huge, and it could help mankind to understand the nanoscale world.